2020
DOI: 10.1101/2020.11.08.20227967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A gender comparison of the psychological distress of medical students in Nigeria during the Coronavirus pandemic: A cross-sectional survey

Abstract: BackgroundThe Coronavirus disease (COVID-19) pandemic as a large scale stressor could have negative distress on the mental health on medical students. Since gender differences in mental health may exist between males and females, it would prove interesting to see if a large scale stressor such as the pandemic will cause variances in the psychological distress between both genders.This study assessed and compared the psychological distress of COVID-19 among male and female medical students in medical schools in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…These findings are similar to the previous studies where females showed higher psychological distress scores. [21][22][23] These findings were also echoed in a Nationwide survey of psychological distress among Chinese people in the COVID 19 epidemic. 24 Response and responsiveness to stress appear to be different by gender.…”
Section: Discussionmentioning
confidence: 72%
“…These findings are similar to the previous studies where females showed higher psychological distress scores. [21][22][23] These findings were also echoed in a Nationwide survey of psychological distress among Chinese people in the COVID 19 epidemic. 24 Response and responsiveness to stress appear to be different by gender.…”
Section: Discussionmentioning
confidence: 72%
“…Sex was the most reported demographic variable. Most studies indicated higher levels of anxiety among females compared to males ( 27 , 28 , 30 , 35 , 43 , 45 50 , 54 , 59 , 60 , 63 , 68 70 , 72 , 73 , 75 , 81 , 83 , 94 , 95 ) with the exception of one study which demonstrated an association between anxiety and being male ( 38 ). Urban residency ( 52 , 62 , 69 , 81 , 83 ), living alone (without family) and lower family income or socioeconomic status were also identified as risk factors for anxiety ( 35 , 44 , 48 , 49 , 69 ).…”
Section: Resultsmentioning
confidence: 97%
“…Among the various healthcare professions, medical laboratory work was significantly associated with higher anxiety compared to others (AOR = 2.75, 95% CI: 1.78–4.79) ( 47 ). Younger age ( 30 , 35 , 45 , 54 , 67 , 71 , 72 , 76 , 79 , 82 , 83 , 85 ), being a widow or single ( 38 , 42 , 67 , 73 ), being unemployed ( 38 , 67 , 73 ) and being a student ( 35 , 52 , 71 ) were also significantly associated with COVID-19 related anxiety. Additionally, negative use of religious coping mechanisms was significantly associated with greater anxiety ( 36 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations